COVID-19 related multisystem inflammatory syndrome in children: a case series from a tertiary care hospital - Prashanth, Badam; Uppalapati, Tanmayi; Erregowda, Adarsh (International Journal of Research in Medical Sciences, 2023)
Multisystem inflammatory syndrome in children (MIS-C) is a rare but serious medical condition associated with COVID-19. Approximately 40-50% of children with MIS-C meet criteria for complete or incomplete Kawasaki disease (KD). In this study, we aim to review and summarize the clinical presentation, laboratory parameters, outcome and management of MIS-C cases presenting to a tertiary care pediatric hospital of RRMCH. Here we report the case series of 7 children diagnosed with MISC. To study the clinical presentation, laboratory parameters, outcome and management of MIS-C cases presenting to a tertiary care pediatric hospital, RRMCH. Retrospective observational study done for a period of 10 months from June 2021 to March 2022. Detailed history taking, clinical examination, laboratory workup, management and outcome recorded were studied. During this period, a total of 22 children were positive for COVID-19 by RT-PCR, and 7 of these patients fulfilled the WHO criteria for MIS-C and were managed in our hospital. The study showed male preponderance with most common feature of presentation being fever constituting to 85.7%, 100% showing hyper inflammatory status and 4 out of 7 patients having cardiac involvement and zero mortality rate. Due to the increasing trend of post covid complications, strong clinical suspicion is required to diagnose MIS-C. As this condition has severe effects on major systems, awareness among pediatricians is required for timely evaluation and treatment to prevent morbidity and mortality associated with MIS-C.